2004
DOI: 10.1038/sj.ijo.0802753
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, leptin resistance, and the effects of insulin reduction

Abstract: Leptin resistance is a hallmark of obesity, but its etiology is unknown, and its clinical measurement is elusive. Leptin-sensitive subjects have normal resting energy expenditure (REE) at a low leptin concentration, while leptin-resistant subjects have a normal REE at a higher leptin concentration; thus, the ratio of REE:Leptin may provide a surrogate index of leptin sensitivity. We examined changes in REE and leptin in a cohort of 17 obese subjects during experimental weight loss therapy with the insulinsuppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
66
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 31 publications
6
66
0
Order By: Relevance
“…41 The high levels of leptin may result in leptin resistance which appears to be a major factor in obesity. [10][11][12] The main fi nding of this study is that acupressure reduced plasma levels of leptin in overweight and obese participants. Although Hsu et al studied the effects of auricular acupuncture on obese women, we included both genders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The high levels of leptin may result in leptin resistance which appears to be a major factor in obesity. [10][11][12] The main fi nding of this study is that acupressure reduced plasma levels of leptin in overweight and obese participants. Although Hsu et al studied the effects of auricular acupuncture on obese women, we included both genders.…”
Section: Discussionmentioning
confidence: 99%
“…12 The combination of the two mechanisms could explain the obesity: fi rst, the absence of leptin or its receptor leads to uncontrolled food intake in normal people; 2 5-8 second, the leptin resistance that is caused by defects in leptin receptors or the large increase in leptin signals in obese people. [10][11][12] However, obesity is now recognised as a low-grade infl ammatory state that affects iron metabolic pathways through the iron regulatory peptide hepcidin. 13 14 Leptin, as a positive regulator of hepcidin, may improve iron metabolism disorders in obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Some metabolic pathways relating to glutathione may be abnormal in childhood NAFLD: plasma levels of elevated oxidized glutathione (Nobili et al, 2005) or plasma glutathione peroxidase (Mandato et al, 2005) have been found. Hyperleptinemia suggested leptin resistance, typical of obesity (Lustig et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…innumerous studies have described a critical role for leptin (LeP) in the regulation of gonadal function, uterine physiology, pregnancy, and implantation [3,5,10]. LeP dysfunction in both animals and humans is associated with profound metabolic abnormalities including obesity, dyslipidemia and LeP resistance [27]. LeP or its receptor dysfunction is among the answers explaining anovulation during obesity that leads to reproductive problems such as infertility [6].…”
Section: Introductionmentioning
confidence: 99%